Modafinil in sports: ethical considerations - Kaufman K. R.; Gerner, R. (British Journal of Sports Medicine, 2005)
Performance enhancing agents are prohibited in athletic competition so that only athletic skills can determine outcomes. Modafinil is a novel non-addicting psychostimulant approved for treatment of narcolepsy. Does its use, especially for medical indications, violate the Olympic Movement Anti-Doping Code? This is discussed with reference to a current high profile case.